The Incidence of Cervical Disease in Women of Different Age Groups in the Republic of Sakha (Yakutia) - Maria P. Kirillina; Sargylana I. Sofronova; Irina V. Kononova; Anna K. Ivanova; Darima K. Garmaeva; Elena L. Lushnikova (International Journal of Biomedicine, 2019)
The purpose of this study was to investigate the incidence of cervical disease in women of different age groups in the Republic of Sakha (Yakutia). Materials and Methods: The cytological material of the cervix of 7,600 women aged between 18 and 88 years was analyzed in the laboratory of pathomorphology, histology and cytology. The material of the cytological study consisted of smears of cervical mucosa and the cervical canal, stained according to the method of Romanovsky-Giemsa. The study was conducted with subjects grouped according to age: Group 1 (18-29), Group 2 (30-44), Group 3 (45-59), and Group 4 (60-74). Results: According to the results of cytological analysis, inflammatory diseases of the cervix uteri were diagnosed in 4,629/61% cases. Among age groups, the highest rate of inflammatory diseases of the cervix uteri was registered in Group 1 and Group 2. Benign cervical lesions were found in 563/7.4% cases with the highest incidence in Groups 1 and 2. The most frequently diagnosed pathology was squamous cell metaplasia with maximum frequency in Group 2 and Group 1. Cervical intraepithelial neoplasia (or dysplasia) (CIN) was detected in 359/4.7% cases. CIN I, CIN II and CIN III were registered in 220/61.3%, 84/24.5%, and 38/10.6% women, respectively. At the same time, the maximum frequency of dysplasia was noted in Group 1 and Group 2. Thus, results obtained indicate a high incidence of cervical disease in women of reproductive age.